2015
DOI: 10.1016/j.archger.2014.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Influence of socio-demographic features and apolipoprotein E epsilon 4 expression on the prevalence of dementia and cognitive impairment in a population of 70–74-year olds: The InveCe.Ab study

Abstract: The age-specific prevalence rates of dementia vary widely. Studies focusing on specific age groups are needed to provide reliable estimates for healthcare providers and policy makers. We estimated the prevalence of dementia, dementia subtypes and cognitive impairment in "InveCe.Ab" (ClinicalTrials.gov, NCT01345110), a single-step multidimensional population-based study of 70-74-year olds living in Abbiategrasso (Milan, Italy). We also looked for associations with socio-demographic factors and the presence of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 75 publications
0
18
0
4
Order By: Relevance
“…Individuals carrying the ε4 allele have an increased risk of developing AD [51]; in contrast, the ε2 allele is protective [52,53,54]. The same correlation exists for the pcb-Cohort.…”
Section: Discussionmentioning
confidence: 57%
“…Individuals carrying the ε4 allele have an increased risk of developing AD [51]; in contrast, the ε2 allele is protective [52,53,54]. The same correlation exists for the pcb-Cohort.…”
Section: Discussionmentioning
confidence: 57%
“…In our study, we found a higher prevalence of VaD and a lower prevalence of AD. Evidence is supported by a very recent Italian study, InveCe.Ab study [ 33 ]. In fact, Guaita and colleagues have reported that the overall dementia prevalence was 3% (95% CI: 2.1–4.1% ).…”
Section: Discussionmentioning
confidence: 99%
“…InveCe.Ab had a response rate of 80.4%, and no differences in age, birth area, or level of education were found between the responders and the nonresponders [15]. For the purposes of the present study, we excluded individuals who refused medical or neuropsychological assessment and therefore had no definitive diagnosis ( n = 15) and those with a diagnosis of dementia ( n = 39), psychosis ( n = 11), or mental retardation ( n = 2).…”
Section: Methodsmentioning
confidence: 99%